KONTRIBUSI DAYA LEDAK OTOT TUNGKAI TERHADAP HASIL LOMPAT JAUH PADA SISWA SMAN 1 BENAI KABUPATEN KUANTAN SINGINGI - Juita, Ardiah; ', Rahmayatun; ', Ramadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The problem in this study originated from the observation of the author during semester exams and competitions class meeting, the low result of the long jump SMA Negeri 1 Benai District of Kuantan Singingi caused by several factors, namely the explosive power leg muscle. The purpose of this study was to determine how big the contribution of explosive power leg muscle to long jump result on SMA Negeri 1 Benai students District of Kuantan Singingi. This type of research is correlational. The population in this study were students of SMA Negeri 1 Benai District Kuantan Singingi totaling 35 people using techniques that side where all the total population sampled, to obtain research data used vertical jump and long jump. Data were analyzed with simple product moment, to determine the contribution of used frequency determinant. Based on data analysis found that the results obtained explosive power leg muscle had significant corelation with the results of the long jump SMA Negeri 1 Benai students District of Kuantan Singingi, characterized by the results obtained by the rcount (0494)> rtable, (0334) and has contributed Kp = r2 (0.4942) x100% = 24%.Keywords : Explosive Power Leg Muscles, Long Jump